2013
DOI: 10.4028/www.scientific.net/aef.8-9.317
|View full text |Cite
|
Sign up to set email alerts
|

Imagistic Evaluation of the Orthodontics Interfaces

Abstract: In orthodontics, the scientific interest regarding adhesion is focused on optimizing adherents: metallic or aesthetic bracket base conditioning, creating aesthetic brackets with improved mechanical properties, enamel conditioning and artificial surface conditioning (aesthetic veneers and crowns). In order to investigate the interfaces between adherents there are several invasive (destructive) methods such as tensile bond strength tests, shear bond strength tests and microleakage tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Regarding imaging tools, CT, micro-CT, and CBCT, were conventionally used in dentistry. Cosmin et al [ 35 ] reported the analysis of the micro-CT imaging for orthodontic adhesive, with a comprehensive comparison between TD-OCT and micro-CT images, quantitatively analyzing the thickness of adhesive between teeth and bracket. Due to the lack of resolution of the utilized OCT, identifying the defects on the entire orthodontic attachments was challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding imaging tools, CT, micro-CT, and CBCT, were conventionally used in dentistry. Cosmin et al [ 35 ] reported the analysis of the micro-CT imaging for orthodontic adhesive, with a comprehensive comparison between TD-OCT and micro-CT images, quantitatively analyzing the thickness of adhesive between teeth and bracket. Due to the lack of resolution of the utilized OCT, identifying the defects on the entire orthodontic attachments was challenging.…”
Section: Discussionmentioning
confidence: 99%